Application of the precision industrial measurement technology in geometric measurement. Issue 2 (April 2021) - Hu, Chang'an; Li, Wanze; Zhou, Yang; Du, Wenbo; Peng, Yuanhui; Li, Jiangang
Abstract: In recent years, for expanding the productivity and improving the market competitiveness, some methods are carried out, which include new technology, new process, new materials and so on, to constantly improve the precision of geometric measurement in the manufacturing field. In addition to this, a large number of the advanced manufacturing equipment has also been used. In the case of rich field experience, this paper mainly introduces the application of laser tracker, laser interferometer, joint arm type coordinate measuring machine, three-dimensional contour optical scanning measuring instrument in robot, automobile fixture, ground penetrating radar, special-shaped parts scanning and so on.